Descriptive legal analysis of family violence and damage to person in civil peruvian law - Cervantes S., Verónica (2010)
A descriptive study was conducted between family violence and damage of person as variables, from psychology and law interdisciplinary approach. On emphasizes psychological violence, damage to life project, its impact in human being existence and achievement. Family violence is a type of dysfunctional relationship into family that causes damage to person. There is a high prevalence of reports to Public Department in Peru. Probably in the future it will continue increasing, and it is important to think carefully about it and find solutions. We question the legitimacy to act to the person who suffered the damage, because there is a lack of the obvious evidence of suffered damage. So, through techniques and instruments from clinical psychology we can demonstrate connection of causation between happened event and caused damage. The TEPT is the clinical syndrome that better describe victims from family violence. On emphasizes symptoms of experience back and hyperactivity.